Clinical and Radiological Evaluation of Silver Fluorophosphate in the Treatment of Long Bone Fractures in Dogs - H Saradva, Dhruv; J Vadalia, Jignesh; L Parmar, Vijay; T Fefar, Dhaval; R Padaliya, Nilesh (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The objective of this study was to evaluate clinical and radiological effect of silver fluorophosphate for repair of long bone fractures in  dogs. Twelve clinical cases of long bone fractures were divided into two groups having six animals in each group. In group I, long bone  fractures were immobilized using a locking compression plate (LCP), while in group II long bone fractures were immobilized using LCP  along with additional use of silver fluorophosphate granules. Post-surgery, modified Robert Jones bandaging provided limb support.  Antibiotics and analgesics were administered and owners were instructed on wound care and limited movement of dogs for minimum  20 days. Radiographic examination and functional outcome of affected bone examination was carried out on the day of surgery and  then on the 15th, 30th, 45th and 60th day post-operatively. Good clinical outcome in terms of post-operative fracture healing and lameness  score was observed in group I compared to group II. The poor outcome in group II might be due to fracture complexity, sex-specific  and breed-specific behaviour, and limited post-operative care. Post-operative complications observed mainly in group II included self mutilation of the wound, screw dislodgment, plate bending, and bone osteolysis.
Keywords: Dog; Locking compression plate; Long bone Fracture; Radiography; Silver fluorophosphate granules; Surgical management